Reconstruction of Intratelencephalic Neurons in the Mouse Secondary Motor Cortex Reveals the Diverse Projection Patterns of Single Neurons - Lin, Hui-Min; Kuang, Jian-Xia; Sun, Pei; Li, Ning; Lv, Xiaohua; Zhang, Yu-Hui (Frontiers in Neuroanatomy, 2018)
Secondary motor cortex (MOs) plays crucial roles in cognitive and executive processes and has reciprocal connections with numerous cortices in rodents. However, the descriptions of the neuronal morphologies and projection patterns of MOs at the level of single neuron remain lacking, severely hindering the comprehensive understanding of MOs’ wiring diagram. Herein, we used a special adeno-associated virus (AAV) to fluorescently label approximately 80 pyramidal neurons nearby or in MOs and acquired an uninterrupted whole-brain 3D dataset at a voxel resolution of 0.2×0.2×1 μm with a whole-brain fluorescence imaging system (fMOST). Based on our 3D dataset, we reconstructed complete morphologies of 36 individual intratelencephalic (IT) neurons nearby or in MOs and analyzed the projection patterns and projection strengths of these neurons at a single neuron level based on several parameters, including the projection areas, the total number of branches, the fiber length, and the total number of terminal tips. We obtained a neuron with an axonal length of 318.43 mm, which is by far the longest reported axonal length. Our results show that all individual neurons in MOs, no matter in layer 2/3 or in layer 5, display diverse projection patterns and projection strengths, implying that these neurons in same region might be involved in different brain circuits with different intensities. The results lay a solid foundation for exploring the relationship between neuronal morphologies and behavioral functions of MOs at the level of single neuron.